Influence of bolus size and chewing side on temporomandibular joint intra-articular space during mastication. (December 2020) - Jurt, Alice; Lee, Jeong-Yun; Gallo, Luigi M; Colombo, Vera
Highlights: During mastication, TMJ space reduces more on the balancing side. Strong bolus size increase affects TMJ space in chewing movements. While chewing, minimum TMJ space is located laterally on the condylar head. Abstract: Previous studies suggested that, during mastication, magnitude and location of mechanical load in the temporomandibular joint (TMJ) might depend on chewing side and bolus size. Aim of this study was to dynamically measure the TMJ space while chewing on standardized boluses to assess the relationship among minimum intra-articular distances (MID), their location on the condylar surface, bolus size, and chewing side. Mandibular movements of 12 participants (6f, 24±1y.o.; 6 m, 28±6y.o.) were tracked optoelectronically while chewing unilaterally on rubber boluses of 15 × 15 × 5, 15 × 15 × 10, and 15 × 15 × 15 mm 3 size. MID and their location along the main condylar axis were determined with dynamic stereometry. MID were normalized on the intra-articular distance in centric occlusion. Repeated measures ANOVA (α = 0.05) showed that MID were smaller on the balancing (0.74±0.19) than on the working condyle (0.89±0.16) independently of bolus size ( p < 0.0001). MIDs did not differ between 5 and 10 mm bolus thicknesses (0.80±0.17) but increased for 15 mm (0.85±0.22, p = 0.024) and were located mostly laterally, close to the condylar center. This study confirmed higher reduction of TMJ space on the balancing than on the working condyle during mastication. Intra-articular distances increased significantly for the greatest bolus thickness. Loaded areas were located laterally, for both working and balancing joint.